Alterations in the Plasma and Red Blood Cell Properties in Patients with Varicose Vein: A Pilot Study - Lukasz Gwozdzinski; Anna Pieniazek; Joanna Bernasinska-Slomczewska; Pawel Hikisz; Krzysztof Gwozdzinski (Cardiology Research and Practice, 2021)
The varicose vein results from the inefficient functioning of the valves in the lower limb veins, making the blood flow slow down and leading to blood stasis and hypoxia. This type of vein dysfunction might be a result of the development of oxidative stress. We compared oxidative stress markers in the plasma and erythrocytes obtained from peripheral veins and varicose veins in the same patients (glutathione, nonenzymatic antioxidant capacity (NEAC), catalase (CAT) and acetylcholinesterase (AChE) activity, thiols, thiobarbituric acid-reactive substance (TBARS), and protein carbonyls). We found a decrease in NEAC in the plasma obtained from the varicose veins compared to the peripheral veins. We detected a decrease in thiols in the plasma, hemolysate, and plasma membranes and increase in protein carbonyl compounds and TBARS levels in the varicose veins. These changes were accompanied by a decrease in CAT and AChE activity. For the first time, our results show changes in the plasma, erythrocyte membrane, and hemolysate protein properties in varicose vein blood in contrast to the plasma and erythrocytes in peripheral vein blood from the same patients. The increased oxidative stress accompanying varicose vein disease might result from the local inefficiency of the antioxidant defense system.